1987
DOI: 10.1111/j.1469-8137.1987.tb00164.x
|View full text |Cite
|
Sign up to set email alerts
|

The Minimum Photon Requirement for Photosynthesis

Abstract: SUMMARYVariations in the apparent photon requirement for photosynthesis (cb,) o"" (^ol) ^^ *^^ ^^^ô f Warburg & Burk (1950) and Yuan, Evans & Daniels (1955) can be ascribed to changes in O2 uptake and energy-dependent processes which result in aberrant photon requirements in organisms subjected to non-optimal conditions. The increase in 05, with increases in the gas exchange quotient (7) in the observations of Yuan et al. (1955) is consistent with increases in photorespiratory production of glycollate, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Unlike the data reported by Bjorkman & Demmig (1987) and Evans (1987) a Kok-effect (Kok 1949) was observed with all the species examined. Whilst the reason for this difference is not known it is unlikely to complicate assessments of 0^ in this work, as these were calculated from measurements made above the light compensation point (see Osbome and Geider 1987a). No correlation was found between leaf absorptance or chlorophyll content and 0^ or 0^, consistent with white light determinations made by Bjorkman & Demmig (1987) and Frost-Christensen & Sand-Jensen (1992).…”
Section: Discussionsupporting
confidence: 52%
“…Unlike the data reported by Bjorkman & Demmig (1987) and Evans (1987) a Kok-effect (Kok 1949) was observed with all the species examined. Whilst the reason for this difference is not known it is unlikely to complicate assessments of 0^ in this work, as these were calculated from measurements made above the light compensation point (see Osbome and Geider 1987a). No correlation was found between leaf absorptance or chlorophyll content and 0^ or 0^, consistent with white light determinations made by Bjorkman & Demmig (1987) and Frost-Christensen & Sand-Jensen (1992).…”
Section: Discussionsupporting
confidence: 52%
“…the progressive inhibition of respiration by photosynthesis with increasing light intensity (6). The inflection occurs in this case above the light-compensation point, a situation that usually happens when the CO2 concentration is high (10,14). The Kok effect in cyanobacteria has been reported and studied by several groups, the general idea being that it relies on the fact that the respiratory and the photosynthetic electron transport chains are closely linked and even share some of their components, such as the plastoquinone pool or the Cyt b/c complex (1,3,12,13).…”
Section: Resultsmentioning
confidence: 99%
“…Some conclude that the minimal quantum requirement is 5 to 6 hv/O z in wild-type green algae (17,18). Such values, if correct, cannot be explained by the Z scheme as it predicts a quantum requirement of at least 8 hv/O z .…”
mentioning
confidence: 99%
“…Pathway studies with the chemical inhibitors 3 [3,4-dichloropheny 1] -1,1-dimethylurea, 2,5-dibromo-3-methyl-6isopropyl-p-benzoquinone, 2-n-nonyl-4-hydroxyquinoline-N-oxide, and carbonyl cyanide-p-trifluoromethoxyphenylhydrazone indicated that in PSII photosynthesis, electron flow from PSII to Fd/NADP + reduction is through the plastoquinone pool and the cytochrome b/f complex (19). When both practical energy loss (such as a loss of about 15% excitations in PSII antenna) and involvement of PSI activity (such as PSI cyclic photophosphorylation) are considered, a quantum requirement (4 hv/O z ) for PSII photosynthesis can explain the reported values of 5 to 6 hv/O z in wild-type green algae (17,18). The previously reported quantum requirement (5 to 6 hv/0 2 ) may suggest that PSII photosynthesis can occur even in wild-type algae.…”
mentioning
confidence: 99%